From Waste Reduction to Worker Comfort: Leveraging Lean Manufacturing and Ergonomics in Textiles Sewing Industries in UAE - ALAM, SAUD AMIR (2024)
Founded in 2005, Prints Textile Factory is an enterprise that leverages quality movement to create, manufacture, and distribute luxury textile clothing for a variety of markets. There are 50-100 employees in the factory. Over the past 19 years, the company has experienced substantial expansion in terms of sales, revenue, human resources, and import/export volumes. The company presently runs manufacturing facilities: a standalone eco-tannery, a cutting-edge knitting, and a garment factory with up to 2 floors. Prints textile Factory leads the workwear market in Ajman and is a well-known producer across United Arab Emirates. Lean manufacturing has a huge impact on raising productivity. Lean principles are designed to identify and eliminate waste, which can result in significant productivity gains. By streamlining processes, reducing lead times, and increasing efficiency, organizations can produce more output with the same or fewer resources. The lean manufacturing approach is now being studied by industrial firms all over the world. According to this study, prints textile factory is dealing with a number of difficulties specific to the sector, including a large number of individual activities, operational sequences, required non-value-added operations, manual labour, etc. These issues are starting to appear in the sewing section. This project focuses on lean manufacturing techniques like the Yamazumi Chart, Kaizen, and 5S. Therefore, in this research, the novel manufacturing of the lean implementation to increase productivity is proposed. The goal of this project is to make use of these technologies and develop an integrated strategy. Utilizing ergonomics principles in the textile industry at " Prints textile factory." will help to achieve SDGs goal 8 (Decent Work & Economic Growth) by minimizing abnormality in organizations while improving productivity goals 12 (Responsible Consumption and Production).